2013 IEEE 10th International Symposium on Biomedical Imaging 2013
DOI: 10.1109/isbi.2013.6556579
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of follicular variant papillary thyroid carcinoma in a rodent model using spectral-based quantitative ultrasound techniques

Abstract: Although thyroid cancer has relatively good prognosis, the management of this disease is complicated by the large incidence of thyroid nodules in the adult population. Unfortunately, current imaging methods do not provide a sufficient level of accuracy in order to replace biopsy as a tool for diagnosis of thyroid cancer. A relatively recent study suggests that spectral-based quantitative ultrasonic methods may provide a new source of contrast when imaging thyroid nodules. In this study, two parameters (i.e., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In previous studies, the FV-PTC and PTC groups in mouse models were identified using ESD and EAC [4,10]. However, these estimators could not differentiate the C-cell adenomas from the normal thyroids.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the FV-PTC and PTC groups in mouse models were identified using ESD and EAC [4,10]. However, these estimators could not differentiate the C-cell adenomas from the normal thyroids.…”
Section: Discussionmentioning
confidence: 99%